Know thy donor: a qualitative study investigating the experiences of living kidney donors at Tygerberg Hospital, Cape Town, South Africa - Hellig, Julian C; Scott, Chantelle J; van der Merwe, Andre (African Journal of Nephrology, 2024)
This study aimed to understand the experiences of living renal donors at Tygerberg Hospital, a tertiary referral hospital in Cape Town, South Africa. A qualitative, descriptive phenomenological study design was used. Semistructured interviews were conducted with 12 kidney donors and transcribed verbatim. Thematic analysis was used, and the main themes that illustrated the donors’ motivation to provide their organs were: 1) to save a life, 2) interpersonal relationships and family acceptance, 3) selfless unsung heroes, 4) life after donation – it goes on, and 5) no regrets. Our findings highlight the positive overall experience of donors.